The Effects of Climate Change Information on Charitable Giving for Water Quality Protection: A Field Experiment. (29th July 2016) - Ellis, Sean F.; Fooks, Jacob R.; Messer, Kent D.; Miller, Matthew J.
Abstract : This study uses a field experiment involving 251 adult participants to determine which messages related to climate change, extreme weather events, and decaying infrastructure are most effective in encouraging people to pay more for investments that could alleviate future water-quality risks. The experiment also assesses whether people prefer the investments to be directed toward gray or green infrastructure projects. Messages about global warming induced climate change and decaying infrastructure lead to larger contributions than messages about extreme weather events. The results suggest that people are likely to pay more for green infrastructure projects than for gray infrastructure projects.